Heat transfer characteristics of a battery liquid-cooling system based on inverted T-shaped oscillating heat pipe with nanofluids - Lu, Hongkun; Noor, M. M.; K., Kadirgama; Beg, M. S. (Faculty Mechanical Engineering, UMP, 2025)
Developing efficient and reliable battery thermal management systems (BTMS) has emerged as a key focus in EV research. The oscillating heat pipe (OHP) is a relatively new technology in BTMS applications. This study proposes a novel hybrid BTMS based on an inverted T-shaped OHP to enhance the heat transfer performance through the coupling of liquid cooling with OHP cooling. Equivalent thermal resistance experiments were used to comprehensively analyze the effect of graphene nanofluid coolant on the hybrid BTMS. The results indicate that increasing the concentration of graphene nanofluids further improves the cooling performance of the hybrid BTMS. At 280W with a concentration of 0.2 wt%, the equivalent BTMS thermal resistance (RBTMS) and maximum temperature (Tmax) are reduced by 20.2% and 32.9%, respectively. However, increasing nanofluid concentration weakens the forced convection effect of the working fluid between the evaporation and condensation sections of the OHP, thereby decreasing the OHP's heat transfer performance within the BTMS. This study deepens the comprehension of the performance enhancement effects of nanofluid coolant in the hybrid system, providing practical guidance for OHP-based cooling system development.